(3GdQjMGf aj efGbH GdfYeGfs
(3ChdgG (B:s
(3GdMeO ddg dGPi CfRd ef GdSeGA eGA JLGLkG s
(3BNQgG (B:s
(3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3PcQ GdeDda Cfg cJH ELGHI dWdH HYV aLeY dge fHfI ef efGbH GdEeGe CHj MfjaI GdfYeGfs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B149 s
Keywords: (3GdJGQjNs